Ceratobasidium ramicola IBRLCM127, an endophytic fungus isolated from Curcuma mangga Valeton & Zijp with strong anti-candidal activity - Kharul Azmi Muazzam Abdul Rahman, Darah Ibrahim (Journal of Applied Pharmaceutical Science, 2019)
Ceratobasidium ramicola IBRLCM127, an endophytic fungus isolated from the rhizome of the local medicinal plant Curcuma mangga Valeton & Zijp, was found to possess significant anti-candidal activity. This fungal endophyte was cultivated in submerged fermentation system using yeast sucrose medium supplemented with host plant water extract and cultivated at 25°C, agitated at 120 rpm for 12 days. The ethyl acetate was used as a solvent to extract compounds in the fermentative broth. The fungal ethyl acetate extract demonstrated significant inhibitory zones toward cells of Candida albicans with minimum inhibitory concentration (MIC) value of 2.5 mg/ml, of which exerting yeastocidal effect. The time–kill study conducted at three distinct ethyl acetate concentrations (half MIC, MIC, and 2 MIC values) revealed that the growth of C. albicans cells was concentration-dependent. Yeastostatic activity was shown at lower concentration and yeastocidal activity was shown at higher concentration. The structural degeneration of the C. albicans cells after treated with ethyl acetate extract was observed under the scanning and transmission electron microscopes and the results exhibited various cell deformities including severe damage of the cell extracellularly and intracellularly which led to cell death beyond repair, thus suggesting that the extract could be a potential antifungal agent.
Keywords: Ceratobasidium ramicola IBRLCM127, endophytic fungus, anti-candidal activity, Curcuma mangga, Candida albicans